Carbon Dot–Doped Titanium Dioxide Sheets for the Efficient Photocatalytic Performance of Refractory Pollutants - Shen, Shen; Li, Rong; Wang, Hongbo; Fu, Jiajia (Frontiers in Chemistry, 2021)
Broad solar light harvesting and fast photoinduced electron–hole migration are two critical factors for the catalytic capacity of photocatalytic system. In this study, novel visible light–driven carbon dot–TiO2 nanosheet (CD-TN) photocatalysts are successfully prepared by loading CDs on the surface of TNs through the hydrothermal method. The microstructure, chemical components, and optical properties of the prepared samples are characterized via X-ray diffraction, Fourier transform infrared spectroscopy, transmission electron microscopy, UV-visible diffuse reflectance spectroscopy, and X-ray photoelectron spectroscopy analysis. Congo red (CR), rhodamine B (RhB), and tetracycline (TC) are selected as pollutants to assess the catalytic performance of CD-TNs. As expected, the removal efficiencies of CD-TNs for CR, RhB, and TC are 94.6% (120 min), 97.2% (150 min), and 96.1% (60 min), respectively, obviously higher than that of pure TNs. The enhanced degradation efficiency of CD-TNs is predominantly ascribed to the merits of CDs (excellent up-conversion property and electron transfer property). Moreover, according to the several degradation cycles, CD-TNs possess the excellent stability, having removed 93.3% of CR after 120 min irradiation.